Black Architects and History: Georgia Brown, São Paulo Metropolitan Area and his Ghosts - Casemiro, Juan; Lira, José Tavares Correia de (Risco - Journal of Architecture and Urbanism, 2021)
This article aims to discuss the silence of architectural historiography around the work of black or women architects and urban planners in Brazil. Taking as a guide the trajectory of the U.S. black architect Georgia Louise Harris Brown, who moved to Brazil in 1953 and worked in Sao Paulo throughout the second half of the 20th century, it is not only a question of observing how her work intersects with her condition of race, gender and nationality. But also to understand how her recruitment by different engineering and construction companies allowed her to intervene in the process of metropolization in a doubly subtle way: as an invisible part of a more complex productive device in the conversion of Greater São Paulo into one of the most dynamic industrial areas in the country, and as a way of building the city without the specialized reference of urban planning.